Interpersonal Communication in Assisting Online-Based Learning at Elementary School: A case of Islamic Educational Subject - Ardiyansyah Ardiyansyah; Ayu Nurkhayati (Jurnal Studi Sosial dan Politik, 2025)
The policy of online-based learning was first introduced by the Ministry of Education and Culture (Kemendikbud) in March 2020. This policy was implemented for all levels of education and was an important step to ensure that students could continue their education, even in crisis situations. It also offered opportunities for innovation and improvement in education in the future. This research aimed to investigate the patterns of interpersonal communication between parents and their children during online learning. The study used a qualitative exploratory method, collecting primary and secondary data through observation and interviews. The study informants were parents of elementary school students in grades 1 and 2. The results showed that during online learning, parents always accompanied and taught their children to be open about their experiences and feelings. They supported their children by motivating and appreciating them, behaving positively to make them feel comfortable during the learning process, showing empathy by understanding their children's feelings during difficulties or boredom, creating a sense of togetherness by respecting and appreciating everything their children did. Interpersonal communication between parents and children became closer because they had more time together. However, parents also experienced communication barriers in accompanying their children's online learning, such as a lack of ability to convey or explain material and a lack of time to accompany their children's learning due to work.